PENGARUH BRAND IMAGE DALAM MEMEDIASI ELECTRONIC WORD OF MOUTH TERHADAP PURCHASE INTENTION PADA PENGGUNA TRAVELOKA - Parama A.P, Dewa Agung; Seminari, Ni Ketut (E-Jurnal Manajemen; Vol 9 No 1 (2020)DO - 10.24843/EJMUNUD.2020.v09.i01.p08, 2020)
This research was conducted in Denpasar City. The number of samples taken is 110 people who intend to use traveloka services, the method of determining the sample used is purposive sampling, and analysis of the data used is path analysis and sobel test. based on the results of the analysis found that electronic word of mouth has a positive and significant effect on brand image, electronic word of mouth has a positive and significant effect on purchase intention, brand image has a positive and significant effect on purchase intention, and brand image has a role in mediating electronic word influence of mouth towards purchase intention. Keywords : brand image, electronic word of mouth, purchase intention